2020
DOI: 10.4103/jfmpc.jfmpc_321_20
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of serum effusion albumin gradient and Light's criteria to differentiate exudative and transudative pleural effusion

Abstract: Context: The incidence of pleural effusion is approximately one million per year. For diagnosing and treatment plan, pleural effusions have to be classified into transudate and exudate. If the diagnosis is not appropriate, it may result in severe complications. The established criterion for differentiating exudates from transudates is Light's criteria. But there were some false positive results in case of transudative effusions when Light's criteria were used. Aims: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…The present study show analysis of biochemical parameters (LDH, pH, Glucose, Triglycerides, Cholesterol, Creatinine, Amylase and ADA) in both pleural fluid and serum. Results of present study were consistent with the other study conducted by Sandeesha V et al (2020), 5 Das AK et al (2009), 6 Burgess LJ et al (1995), 7 Dhar MC et al (2000). 8 According to present study Lights criteria's specificity for exudate was 96.43% and sensitivity was 100%.…”
Section: Discussionsupporting
confidence: 92%
“…The present study show analysis of biochemical parameters (LDH, pH, Glucose, Triglycerides, Cholesterol, Creatinine, Amylase and ADA) in both pleural fluid and serum. Results of present study were consistent with the other study conducted by Sandeesha V et al (2020), 5 Das AK et al (2009), 6 Burgess LJ et al (1995), 7 Dhar MC et al (2000). 8 According to present study Lights criteria's specificity for exudate was 96.43% and sensitivity was 100%.…”
Section: Discussionsupporting
confidence: 92%
“…All patients with heart failure who had been misclassified as having exudates based on Light’s criteria were correctly classified using the albumin gradient calculation. Sandeesha et al 27 reported results with a similar study based on 66 patients. Twenty of 22 patients with transudates and 41 of 44 patients with exudates were correctly classified using this gradient.…”
Section: Pleural Effusion Analysis Using Nt-pro-bnp and Serum To Flui...mentioning
confidence: 80%
“…Exudative pleural effusion diagnosed first by using Light's criteria, suggesting that pleural effusion is an exudate if effusion protein/serum protein ratio greater than 0.5 and, effusion lactate dehydrogenase (LDH)/serum LDH ratio greater than 0.6, or pleural fluid LDH concentration is less than 2/3 of the upper reference limit. 1…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…But results may be false positive may occur in patients with transudative effusions when (Light's criteria) were applied. 1 The cholesterol level of pleural fluid can be used as a variable in diagnosing effusion of exudative natur eand even can replace (Light's criteria). Approaches to diagnos epleural effusion patients must be precise as multiple procedures depend on nature and analysis of the effusion fluid.…”
Section: Introductionmentioning
confidence: 99%